Perbandingan Asupan Makan Dan Aktifitas Fisik Pada Remaja Berdasarkan Status Gizi : Comparison of Food Intake and Physical Activity in Adolescents Based on Nutritional Status - Susmiati; Nur Indrawaty Lipoeto; Zifrianthi Minanda Putri (Fakultas Keperawatan Universitas Andalas, 2020)
To date, the cause of obesity is unclear and debatable. Effective treatment and prevention of obesity is achievable if its pathogenesis is known comprehensively. The objective of this research is to study and compare dietary intake and physical activities among adolescents between obese and normal ones. The study is conducted by case-control with 311 samples of female adolescents. Sampling was conducted by stratified random sampling. Obesity criterion was based on BMI > 2 SD and normal -2 SD 1 SD. Dietary patterns was determined using semi quantitative Food Frequency Questionnaire (FFQ) and physical activity was determined by Physical Activity Questionnaire for Older Children (PAQC). Average total energy intake on the obese was 2344,92± 606,31 kcal/day, higher than that of the normal group (2285,41± 602,86 kcal/day), but there was no significant difference between the two groups (p=0.435). Among subjects with mild physical activities, 62.9% were obese, whereas 58.9% were in normal group. There was no significant relationship between physical activities and obesity (p=0.27). Average intake of carbohydrates, protein, fat, fiber, and fatty acid is higher on those with high physical activities than those with moderate and low physical activities. There was a significant relationship between dietary intake and physical activities with p<0.05. In conclusion, there was no difference between dietary intake and physical activities based on nutritional status on adolescents.